Speech by the UM Rector Professor Zdravko Kačič, PhD 15th Anniversary of the Faculty of Medicine of the University of Maribor / Nagovor rektorja UM prof. dr. Zdravka Kačiča 15. obletnica Medicinske fakultete UM - Kačič, Zdravko (Acta Medico-Biotechnica, 2021)
We know how important health is and that it is associated with a healthy lifestyle. That is why we understand the meaning of the Latin proverb: “If you lack a physician, let your physicians be a light-hearted soul, rest and moderate life”. However, nowadays in the urban environment of a developed society, when almost everything is available to us, it is hard to imagine the difficulties of millions of people across the world, who lack fundamental health care services. Similarly, it is hard to imagine, for example, the situation of one of the most important medieval reformers of medicine, Paracelsus, who after completing his medical studies, travelled and was “a travelling healer” and claimed that “a physician has to be a traveller who must look for old women, Romanies, magicians, vagrants, old bandits and similar outcasts, from whom one can learn much”.